The Effect of Emotional Intelligence and Leadership Styles on Job Satisfaction - MONUS, Yeşim; AYHÜN, Sena ERDEN (Foundations of management, 2024)
The objective of this study is to determine the effect of transformational and transactional leadership styles applied by senior managers to the employees working in different positions in Turkey on their job satisfaction behaviors. Moreover, the study also aims to determine the effect of employees' perceptions of emotional intelligence on job satisfaction behaviors. In addition, the mediating role of emotional intelligence in the effect of transformational and transactional leadership styles on job satisfaction behaviors was examined as well. In line with this objective, a questionnaire study was conducted on 542 employees working in different positions in private and public sectors. Research findings demonstrate that transactional and transformational leadership styles and emotional intelligence positively affect job satisfaction. However, the mediating role of emotional intelligence in the relationship between transactional and transformational leadership styles and job satisfaction was not determined.